Firm heterogeneity in food safety provision: Evidence from aflatoxin tests in Kenya - Moser, Christine; Hoffmann, Vivian; Ordonez, Romina (Agricultural and Applied Economics Association, 2014)
How can food safety be provided in the absence of regulatory enforcement? What can explain heterogeneous responses to unenforced regulation across firms when certain food safety characteristics are unobservable to the consumer? Using data from over 900 maize flour samples representing 23 distinct brands in eastern and central Kenya, this paper explores the relationship between price, brand and aflatoxin contamination. Aflatoxin is a toxin common in maize, groundnuts and other crops around the world and, while it is unobservable to the consumer, it may be correlated with other quality characteristics. We find a strong negative correlation between price and contamination rates, which is consistent with certain brands investing more in quality to avoid loss of reputational capital.